Cotransfer of circular and linear prokaryotic and eukaryotic DNA sequences into mouse cells. - Hsiung, N (1980)
We have attempted to introduce some eukaryotic and prokaryotic DNA sequences into mouse fibroblasts. Purified herpes thymidine kinase gene (tk) was introduced into mouse cells. The presence of the herpes tk gene was established by gel electrophoresis, sensitivity to the purine analog acyloguanosine, and Southern blot hybridization. We utilized two different methods to introduce nonselectable markers into mouse cells. Bacterial plasmid pBR322 was ligated to herpes tk and used for transfection. All cells that were TK+ also contained the plasmid sequences. In the second method, pBR322 DNA was mixed with herpes tk DNA and presented to mouse cells. TK+ cells were tested for pBR322 sequences by blot hydridization. The frequency of unlinked cotransfer was greater than 40%. When the circular plasmid containing pBR322 and tk was used for transfection, each of the resulting transfectants acquired several copies of the plasmid. Most of the copies were associated with high molecular weight DNA in the cell. In addition, we found that some of the plasmid molecules may exist as free circular molecules. Using the nonligated cotransfer method, we introduced purified human beta-globin sequences into the recipient cells. We were unable to detect any transcripts of the human beta-globin gene at a level greater than or equal to 10 molecules per cell.